Smartphone Psychological Therapy During COVID-19: A Study on the Effectiveness of Five Popular Mental Health Apps for Anxiety and Depression - Marshall, Jamie M.; Dunstan, Debra A.; Bartik, Warren (Frontiers in Psychology, 2021)
The aims of this study were to examine the effectiveness of a range of smartphone apps for managing symptoms of anxiety and depression and to assess the utility of a single-case research design for enhancing the evidence base for this mode of treatment delivery. The study was serendipitously impacted by the COVID-19 pandemic, which allowed for effectiveness to be additionally observed in the context of significant community distress. A pilot study was initially conducted using theSuperBetter app to evaluate the proposed methodology, which proved successful with the four finishing participants. In the main study, 39 participants commenced (27 females and 12 males,MAge = 34.04 years,SD = 12.20), with 29 finishing the intervention phase and completing post-intervention measures. At 6-month follow-up, a further three participants could not be contacted. This study used a digitally enhanced, multiple baseline across-individuals single-case research design. Participants were randomly assigned to the following apps:SuperBetter (n = 8),Smiling Mind (n = 7),MoodMission (n = 8),MindShift (n = 8), andDestressify (n = 8). Symptomatology and life functioning were measured at five different time points: pre-baseline/screening, baseline, intervention, 3-week post-intervention, and 6-month follow-up. Detailed individual perceptions and subjective ratings of the apps were also obtained from participants following the study’s completion. Data were analyzed using visual inspection, time-series analysis, and methods of statistical and clinical significance. Positive results were observed for all apps. Overall, more favorable outcomes were achieved by younger participants, those concurrently undertaking psychotherapy and/or psychotropic medication, those with anxiety and mixed anxiety and depression rather than stand-alone depression, and those with a shorter history of mental illness. Outcomes were generally maintained at 6-month follow-up. It was concluded that a diverse range of evidence-based therapies offered via apps can be effective in managing mental health and improving life functioning even during times of significant global unrest and, like all psychotherapies, are influenced by client features. Additionally, this single-case research design is a low-cost/high value means of assessing the effectiveness of mental health apps. Clinical Trial Registration: The study is registered with the Australian and New Zealand Clinical Trials Registry (ANZCTR), which is a primary registry in the World Health Organization Registry Network, registration number ACTRN12619001302145p (http://www.ANZCTR.org.au/ACTRN12619001302145p.aspx).